Thematic Information Clusters for Integrated GIS Mapping of the Marine Ecosystems - Lemenkova, Polina (2015)
This work presents a methodology developed structure of the information clusters for mapping the marine ecosystems. A case study is given by an example of the Arctic seas. The research has been made using geographic information technologies for environmental monitoring of the marine areas. The proposed method of the marine environmental mapping is suggested at scale 1: 1, 5 million- 1:20 million. It is intended mostly for the environmental institutions for the design and creation of environmental maps. The research is aimed at the environmental control and monitoring of the Arctic sea basin. The maps included in the information clusters and can be used as a basis for monitoring environmental risks, modeling dynamics of the marine ecosystems, especially in the area of intensive anthropogenic impacts (e.g. offshore oil works and in shelf areas). Настоящая работа представляет разработанную методику по организации структуры информационных блоков для картографирования морских экосистем на примере морей Арктики с использованием геоинформационных технологий для мониторинга экологического состояния морских акваторий. Предложенная методика морского геоэкологического картографирования в масштабах 1:5млн-1:20млн предназначена в первую очередь для природоохранных институтов, занимающихся проектированием экологических карт и осуществлением экологического контроля и мониторинга морских бассейнов. Карты, входящие в информационные блоки и составленные по данной методике, могут служить основой для решения задач моделирования динамики морских экосистем в зоне особо интенсивного антропогенного воздействия (например, на шельфе и очагах нефтедобычи). info:eu-repo/semantics/published